Investigation of the Impact of Active Layer and Charge Transfer Layer Materials on the Performance of Polymer Solar Cells through Simulation - Fekadu Gochole Aga; Fetene Fufa Bakare; Solomon Tiruneh Dibaba; Demissie Jobir Gelmecha; Chernet Amente (Advances in Materials Science and Engineering)
This article reports polymer solar cell performance evaluated using general-purpose photovoltaic device model (GPVDM) software for various device structures. The essential parameters of the cell such as short circuit current density (JSC), open-circuit voltage (VOC), fill factor (FF), and power conversion efficiency (PCE) are evaluated for these structures. The simulation result shows the performance of the cells could be highly affected by both interfacial and active layers. Among the demonstrated device structures, better performance is observed for device structure ITO/V2O5/PTB7 : PC70BM/TiOx/Al with 10.4 mA/cm2 short circuit current density, 0.89 V open-circuit voltage, 59.5% fill factor, and 6.1% power conversion efficiency. The study is useful for a better understanding of the powerful effect of the materials in the device structure on the performance of the cell and thereby determines the proper device structure and materials for improving the performance of the cell.